2017
DOI: 10.1038/s41598-017-05992-9
|View full text |Cite
|
Sign up to set email alerts
|

Mapping resistance responses to Sclerotinia infestation in introgression lines of Brassica juncea carrying genomic segments from wild Brassicaceae B. fruticulosa

Abstract: Sclerotinia stem rot (Sclerotinia sclerotiorum) is a major disease of Brassica oilseeds. As suitable donors to develop resistant cultivars are not available in crop Brassicas, we introgressed resistance from a wild Brassicaceae species, B. fruticulosa. We produced 206 B. juncea-B. fruticulosa introgression lines (ILs). These were assessed for pollen grain fertility, genome size variations and resistance responses to Sclerotinia following stem inoculations under disease-conducive conditions. Of these, 115 ILs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 68 publications
2
45
0
Order By: Relevance
“…The majority of commercial oilseed rape varieties in Australia are susceptible to SSR (Uloth et al, 2015;Rana et al, 2017). However, a growing list of publications show that partial, quantitative resistance exists in B. napus germplasm and many of its close relatives (Mei et al, 2011;Uloth et al, 2013Uloth et al, , 2015Taylor et al, 2015;Rana et al, 2017). In some cases, resistance has been identified by inoculation of the main stem of adult plants (Buchwaldt et al, 2005;Gyawali et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of commercial oilseed rape varieties in Australia are susceptible to SSR (Uloth et al, 2015;Rana et al, 2017). However, a growing list of publications show that partial, quantitative resistance exists in B. napus germplasm and many of its close relatives (Mei et al, 2011;Uloth et al, 2013Uloth et al, , 2015Taylor et al, 2015;Rana et al, 2017). In some cases, resistance has been identified by inoculation of the main stem of adult plants (Buchwaldt et al, 2005;Gyawali et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…; Rana et al . ). In general, different parts of sunflower plant display independent types of tolerance to S. sclerotiorum infection (Tuorvieille and Vear ).…”
Section: Introductionmentioning
confidence: 97%
“…Earlier studies suggested that resistance to S. sclerotiorum is polygenic in nature (Cheng et al 2009;Rana et al 2017). In general, different parts of sunflower plant display independent types of tolerance to S. sclerotiorum infection (Tuorvieille and Vear 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the wild species typically have higher resistance to abiotic and biotic stresses in comparison with cultivated peanut (Brasileiro et al, 2015; Han et al, 2017; Michelotto et al, 2017). Several successful cases were reported on introgression of disease resistance from wild‐type species into cultivated crops through interspecific hybridization such as potato ( Solanum tuberosum ) and brown mustard ( Brassica juncea ) (Boschi et al, 2017; Rana et al, 2017) and peanut (Fávero, Santos, Simpson, Valls, & Vello, 2015; Michelotto et al, 2015; Sharma, Kalia, Singh, & Sharma, 2017; Simpson, Nelson, Starr, Woodard, & Smith, 1993; Stalker & Lynch, 2002). Therefore, a wild species with known resistance to spotted wilt can be used to create peanut interspecific hybrid lines with superior host resistance.…”
Section: Introductionmentioning
confidence: 99%